PENINGKATAN KEMAMPUAN BERBAHASA INGGRIS SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF - Marice Saragih (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
This research is aimed to increasing the students’ ability in speaking skills through Cooperative Learning Approach. The subject was the second grade at the second semester student of Senior high school Methodist 12 Medan, academic year 2018/2019. This study is classroom action research means that this study done in one class in one school. The research instrument used test, observation and questionnaire. The result of this study showed that the value in pretest and posttest increased, it can be seen from the improvement of mean of the students’ score namely: the mean of the pretest was 69.25 increased to the mean of the posttest to the first cycle was 74.89 and the post test in the second cycle was 83.21. The improvement also can be seen from the percentage of the students’ speaking achievement in the pretest only 53.57 %( fifteen students) got 75 point. In the post test in cycle I 78.57 %( twenty two students) got 75 point. It means there was improvement 25 %. In the post test cycle II 100 % (twenty eight students) got 75 points. The improvement was 21.43 %. The conclusion is the cooperative learning approach increases the students speaking ability.